Kyrgyz and Kazakhs in a forgotten horse sport: Valiant chase - Turkmen, M.; Ziyagil, M.A. (Nova Science Publishers, Inc., 2023)
In Kyrgyz, "Dzhigit Kumay" and in Kazakhs "Dzhigit Kuu" as a team and evasion of this game in the form of the chase, Turkey full provision in Turkish "Yigit Kovalama / Valiant Chasing" is. This equestrian game, which is almost forgotten, until 1922-26, was played extensively among the Turkic peoples in all Turkestan geography. To overcome the shortage of resources, which is almost nonexistent in the game, to provide a resource to researchers and future generations on the subject, this game is about to be forgotten, again to add to the national sports ring of the Turks. © 2023 by Nova Science Publishers, Inc. All rights reserved.